Conduct risk within the United States financial sector. (18th August 2020) - Daly, Mary; O Sullivan, Patrick
ABSTRACT: Conduct risk in the Financial Services sector has become an area for research especially since the 2008 financial crisis. New and revised regulations and guidelines are being implemented in an effort to, on the one hand facilitate regulatory censure and on the other hand to guide and ensure better behaviour amongst senior management and their decisions in relation to incentive policies. This paper provides a micro-level examination of conduct risk events within financial institutions sanctioned by the Securities and Exchange Commission. From these risk events a number of internal organisational failings were then extrapolated and categorised, and further conceptualised within the Hofstede cultural perspective of organisational decision-making in relation to financial services behaviour.